Induction of neutrophil chemotaxis by the quorum-sensing molecule N-(3-oxododecanoyl)-L-homoserine lactone - Zimmermann, Sabine; Wagner, Christof; Müller, Wencke Eike; Brenner-Weiss, Gerald; Hug, Friederike; Prior, Birgit; Obst, Ursula; Hänsch, Gertrud Maria (Infection and immunity, 2006)
Acyl homoserine lactones are synthesized by Pseudomonas aeruginosa as signaling molecules which control production of virulence factors and biofilm formation in a paracrine manner. We found that N-(3-oxododecanoyl)-L-homoserine lactone (3OC12-HSL), but not its 3-deoxo isomer or acyl-homoserine lactones with shorter fatty acids, induced the directed migration (chemotaxis) of human polymorphonuclear neutrophils (PMN) in vitro. By use of selective inhibitors a signaling pathway, comprising phosphotyrosine kinases, phospholipase C, protein kinase C, and mitogen-activated protein kinase C, could be delineated. In contrast to the well-studied chemokines complement C5a and interleukin 8, the chemotaxis did not depend on pertussis toxin-sensitive G proteins, indicating that 3OC12-HSL uses another signaling pathway. Strong evidence for the presence of a receptor for 3OC12-HSL on PMN was derived from uptake studies; by use of radiolabeled 3OC12-HSL, specific and saturable binding to PMN was seen. Taken together, our data provide evidence that PMN recognize and migrate toward a source of 3OC12-HSL (that is, to the site of a developing biofilm). We propose that this early attraction of PMN could contribute to prevention of biofilm formation.